Biodegradation of Crystal Violet dye by bacteria isolated from textile industry effluents - Roy, Dipankar Chandra; Biswas, Sudhangshu Kumar; Saha, Ananda Kumar; Sikdar, Biswanath; Rahman, Mizanur; Roy, Apurba Kumar; Prodhan, Zakaria Hossain; Tang, Swee Seong (PeerJ, 2018)
Industrial effluent containing textile dyes is regarded as a major environmental concern in the present world. Crystal Violet is one of the vital textile dyes of the triphenylmethane group; it is widely used in textile industry and known for its mutagenic and mitotic poisoning nature. Bioremediation, especially through bacteria, is becoming an emerging and important sector in effluent treatment. This study aimed to isolate and identify Crystal Violet degrading bacteria from industrial effluents with potential use in bioremediation. The decolorizing activity of the bacteria was measured using a photo electric colorimeter after aerobic incubation in different time intervals of the isolates. Environmental parameters such as pH, temperature, initial dye concentration and inoculum size were optimized using mineral salt medium containing different concentration of Crystal Violet dye. Complete decolorizing efficiency was observed in a mineral salt medium containing up to 150 mg/l of Crystal Violet dye by 10% (v/v) inoculums of Enterobacter sp. CV-S1 tested under 72 h of shaking incubation at temperature 35 °C and pH 6.5. Newly identified bacteria Enterobacter sp. CV-S1, confirmed by 16S ribosomal RNA sequencing, was found as a potential bioremediation biocatalyst in the aerobic degradation/de-colorization of Crystal Violet dye. The efficiency of degrading triphenylmethane dye by this isolate, minus the supply of extra carbon or nitrogen sources in the media, highlights the significance of larger- scale treatment of textile effluent.